PELATIHAN PENGOLAHAN BEKATUL SEBAGAI MAKANAN FUNGSIONAL DALAM PEMBUATAN ANEKA MAKANAN DI KELURAHAN WEDOMARTANI KECAMATAN NGEMPLAK SLEMAN YOGYAKARTA - Auliana, Rizqie (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
Activity program of PPM Reguler about exploiting of rice bran or bekatul as component of food having potency as functional food because content gizi and its the benefit for health in Kelurahan Wedomartani has been compiled dur- ing survey that in location in big supply rice bran. Skilled training processed this rice bran has successfully is executed carefully during 3 times looks in the face in the form of the management of training in a word, that is theory phase, phase practice and motivation phase. Theory matter given is (a) nutrition poten- tial about rice bran for health; (b) knowledge about functional food; (c) prepara- tion and cooking rice bran; (d) sanitary hygiene in processing rice bran; and (e) packaging rice bran product. Theory matter is given [by] during 180 minutes. Practice matter given is processing rice branl to become four barium food products rice bran, that is: rice bran meals, brownies bekatul steam, bekatul ti- wul ayu and bekatul coconut cookies. This matter given during 360 minutes by the way of dividing participant in 4 group. Result from competition in moti- vation phase is obtained [by] 5 food product with addition rice bran is varying either continental food and also traditional food, that is: pudding bekatul young coconut, cake caramel bekatul, good time bekatul cookies, nagasari bekatul and klepon bekatul. This  training  told  is  success  because  has  as  according  to  Indikator success specified, that is training expressed is success if 90% participant follow training till finish and proved from presensi presence, and 80% participant has enough value in information test and skilled so that expressed is creative and can process rice bran to become multifarious of food product at the time of competition. Result of assessment of presence shows result of 99% participant to come to follow training till finish and 96% training participant has know- ledge either. While from position or response to existence of rice bran  86,4% expressed agrees if bekatul is applied as component of nourishment and it is good to is consumed. While evaluating practicing (skilled) has seen more than 60% has owned good ability in preparation, process and presentation, whereas 100% participant has owned creativity.